Persistent operational synchrony within brain default-mode network and self-processing operations in healthy subjects - Fingelkurts, Andrew A.; Fingelkurts, Alexander A. (Brain and cognition, 2011)
Based on the theoretical analysis of self-consciousness concepts, we hypothesized that the spatio-temporal pattern of functional connectivity within the default-mode network (DMN) should persist unchanged across a variety of different cognitive tasks or acts, thus being task-unrelated. This supposition is in contrast with current understanding that DMN activated when the subjects are resting and deactivated during any attention-demanding cognitive tasks. To test our proposal, we used, in retrospect, the results from our two early studies (Fingelkurts, 1998; Fingelkurts et al., 2003). In both studies for the majority of experimental trails we indeed found a constellation of operationally synchronized cortical areas (indexed as DMN) that was persistent across all studied experimental conditions in all subjects. Furthermore, we found three major elements comprising this DMN: two symmetrical occipito-parieto-temporal and one frontal spatio-temporal patterns. This new data directly supports the notion that DMN has a specific functional connotation – it provides neurophysiologic basis for self-processing operations, namely first-person perspective taking and an experience of agency.